Assessment of surface treatment on fatigue life of cylinder block for linear engine using frequency response approach - M.M., Rahman; A.K., Ariffin; M.M., Noor; A.B., Rosli; M.A., Maleque (Science Publications, 2009)
Objectives: This study was focused on the finite element techniques to investigate the effect of surface treatment on the fatigue life of the vibrating cylinder block for new two-stroke free piston engine using random loading conditions. Motivation: An understanding of the effects related to the random loading is necessary to improve the ability of designers to accurately predict the fatigue behavior of the components in service. An internal combustion engine cylinder block is a high volume production component subjected to random loading. Problem statement: Proper optimization of this component that is critical to the engine fuel efficiency and more robustly pursued by the automotive industry in recent years. A detailed understanding of the applied loads and resulting stresses under in-service conditions is demanded. Approach: The finite element modeling and analysis were performed utilizing the computer aided design and finite element analysis codes respectively. In addition, the fatigue life prediction was carried out using finite element based fatigue analysis code. Aluminum alloys were considered as typical materials in this study. Results: The frequency response approach was applied to predict the fatigue life of cylinder block using different load histories. Based on the finite element results, it was observed that the fatigue life was significantly influenced for the nitriding treatment. The obtained results were indicated that the nitrided treatment produces longest life for all loading conditions. Conclusion: The nitriding process is one of the promising surface treatments to increase the fatigue life for aluminum alloys linear engine cylinder block.